Interest-free microfinance in India: a case study of Bait-un-Nasr Urban Cooperative Credit Society - Wasiullah Shaik Mohammed; Khalid Waheed (ISRA International Journal of Islamic Finance, 2019)
Purpose: The purpose of this paper is to understand interest-free microfinance practices in India, identify issues and recommend possible solutions. Design/methodology/approach To achieve the proposed objectives, Bait-un-Nasr (BuN) Urban Cooperative Credit Society, located in Mumbai, India, is considered for the case study. The study is based on both primary and secondary data. The primary data are collected through questionnaires and secondary data from various sources. Performance of the institution is assessed in terms of growth and sustainability indicators. Findings It is found that BuN has been successful in providing interest-free microfinance services in India. A few operational issues have been highlighted and possible solutions are recommended. Moreover, it is found that in comparison to the microfinance industry standards, the performance of BuN has been lower. Research limitations/implications BuN is evaluated from only growth and sustainability aspects and not from the aspect of the socio-economic impacts of its services on the lives of customers. Practical implications This study would become a documented source of interest-free microfinance practices in India. Moreover, the recommendations provided, if implemented, would help BuN in further growth and development. Social implications This study would help create awareness in the society about the practices of interest-free microfinance. Originality/value This paper highlights the interest-free microfinance practices in India that have not received the needed attention. The paper also attempts to identify key issues pertaining to interest-free microfinance with possible solutions.
Keywords: 330; India; Microfinance; Cooperatives; Islamic microfinance; Sharīʿah; Bait-un-Nasr